Modified silicon negative electrode material, preparation method thereof and application of modified silicon negative electrode material in battery

By introducing an anchor-based carba-based carbon nanotubes with transitional metal-carboxyl clusters in the lithium-ion battery material, the cycle life caused by the volume of the lithium and lithium of the silicon negative material in the process of lithium and lithium is solved. The problem of unstable performance realizes higher cycle performance and battery stability.

CN119381432APending Publication Date: 2025-01-28LIONGO (CHANGZHOU) NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411517058.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The volume of the silicon anode material in existing lithium-ion batteries varies greatly during the lithiation and deliquification process, resulting in a shortened cycle life and unstable electrochemical performance.

Method used

The modified silicon negative material is composed of a modified carbon nanotuba covered with silicon oxide and covered with silicon oxide base surface. Nano tube. The carboxyl exchange reactions are anchored on the carbon nanopotranskin with a carboxyl -rich metal single -molecule cluster and covered with the surface of the silicon oxide.

Benefits of technology

This modified silicon negative material is reduced by reducing lithium battery impedance, increasing ionic conductivity and lithium ion diffusion rate, reducing polarization, thereby significantly improving the cycle performance of lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005108633150000151
    Figure BDA0005108633150000151
  • Figure HDA0005108633190000011
    Figure HDA0005108633190000011
  • Figure HDA0005108633190000012
    Figure HDA0005108633190000012
Patent Text Reader

Abstract

The invention belongs to the technical field of battery negative electrodes, and particularly relates to a modified silicon negative electrode material, a preparation method thereof and application of the modified silicon negative electrode material in a battery. The modified silicon negative electrode material comprises a silicon oxide substrate and a modified carbon nanotube coated on the surface of the silicon oxide substrate, wherein the modified carbon nanotube is a carboxylated carbon nanotube anchored with a transition metal-carboxyl cluster compound. In the invention, the carboxyl exchange reaction can be utilized to anchor the carboxyl-rich transition metal monomolecular cluster on the carboxylated carbon nanotube and coat the surface of the silicon oxide, so that the lattice gap can be widened, the impedance of the lithium battery is reduced, the ionic conductivity and the lithium ion diffusion rate are improved, the polarization is reduced, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery negative electrodes, and in particular relates to a modified silicon negative electrode material, a preparation method thereof and an application thereof in a battery. Background Art

[0002] With the rapid development of power source development in my country's spacecraft and advanced weapons and equipment, civilian new energy electric vehicles, and energy storage power stations, the energy density requirements for lithium-ion negative electrodes are increasing. Among the commonly used negative electrode materials for lithium-ion batteries in the above energy systems, silicon materials have the highest theoretical lithium storage capacity (theoretical capacity at room temperature is 3579mAh / g), which is ten times that of the current commercial graphite negative electrode materials (theoretical capacity is 372mAh / g), making it one of the most promising negative electrode materials for high-energy-density lithium-ion batteries. Silicon is abundant in the earth's crust, but it rarely appears in the earth's crust as a single substance. At present, large-scale production of pure silicon is a very mature technology and has been used in solar cells and semiconductor products.

[0003] Unlike the lithiation mechanism of carbon materials, the volume change of the silicon negative electrode is large during the (de)lithiation process, and it needs to undergo multiple crystallographic phase transitions, which will shorten the cycle life of silicon-based lithium-ion batteries and cause battery failure. In addition, crystalline silicon undergoes a phase transition from crystal to amorphous during the first lithiation process under room temperature, and then remains in an amorphous state. According to the lithium insertion mechanism of silicon, it can be seen that even at room temperature, the molar ratio of silicon to lithium is still 4:15. Therefore, embedding a large amount of lithium in the silicon atomic lattice will cause a huge volume change of silicon itself. This volume change will produce uncontrollable stress, and silicon itself cannot withstand its stress, causing cracks in the silicon particles or even pulverization, resulting in rapid decay of the capacity of the silicon negative electrode.

[0004] In addition, the volume of silicon materials will expand to varying degrees during the lithium insertion process, causing the silicon material particles to squeeze each other and deform; and in the lithium removal process, the silicon material will shrink to varying degrees due to lithium removal, causing the silicon particles to separate from each other, the silicon particles from the conductive agent, and the silicon particles from the current collector, and the morphological structure will also change accordingly. After a long period of cycling, the conductive network of the silicon negative electrode will be destroyed and collapsed, and lose electrical contact with the current collector, resulting in unstable electrochemical performance of the silicon negative electrode. In addition to the pulverization of the silicon material and the loss of electrical contact, the huge volume change of the silicon negative electrode during the cycle will also form an unstable solid electrolyte interface.

[0005] In terms of modification of silicon negative electrode materials, hollow and porous structures can significantly reduce volume expansion, thereby improving electrochemical performance. The hollow structure of silicon can shorten the diffusion distance of lithium ions, reduce the maximum stress during lithiation, and improve the cycle performance. Silicon-carbon composite negative electrode materials are one of the hot topics in the field of lithium-ion battery research. Their high theoretical specific capacity (about 4200mAh / g) gives them significant advantages in high energy density batteries. In general Si / C composite systems, Si particles as active materials can fully provide lithium storage capacity, while C can buffer the volume change of silicon, improve the conductivity of silicon-carbon composite negative electrode materials, and avoid agglomeration of Si particles during the cycle. Existing Si / C composite materials combine these two advantages and show high specific capacity and long cycle life. However, the commercial application of silicon-carbon composite negative electrode materials still faces some key technical challenges or defects. The current silicon-carbon negative electrode materials and their preparation schemes cannot completely solve the problem of active material particles rupture and failure of contact with the current collector caused by the expansion of the silicon negative electrode during the cycle. Summary of the invention

[0006] In view of the main defects of the above-mentioned prior art, the present invention provides a modified silicon negative electrode material, a preparation method thereof and application in a battery. The modified silicon negative electrode material provided by the present invention can further improve the cycle performance of lithium-ion batteries.

[0007] The invention provides a modified silicon negative electrode material, comprising: a silicon oxide substrate and modified carbon nanotubes coated on the surface of the silicon oxide substrate, wherein the modified carbon nanotubes are carboxylated carbon nanotubes anchored with transition metal-carboxyl clusters.

[0008] The present invention provides a method for preparing a modified silicon negative electrode material, comprising the following steps:

[0009] S1, mixing silicon oxide and a bonding polymer for reaction, and then embedding the formed particles into the interwoven network structure of carbon nanotubes to obtain a precursor;

[0010] S2, subjecting the precursor to carbonization heat treatment in an inert or nitrogen atmosphere, and then reacting with a mixed acid consisting of concentrated sulfuric acid and concentrated nitric acid to obtain a surface carboxylated silicon-carbon composite;

[0011] S3, forming a modified silicon negative electrode material by subjecting the surface carboxylated silicon-carbon composite to a carboxyl exchange reaction with a transition metal-carboxyl cluster.

[0012] In an embodiment of the present invention, in step S1, the adhesive polymer is polyethyleneimine and polydopamine; the mixing reaction of the silicon oxide and the adhesive polymer comprises: mixing the silicon oxide, polyethyleneimine and dopamine hydrochloride in water, reacting by ultrasonic stirring, and separating and washing to obtain the dispersion after the reaction;

[0013] The particle size of the silicon oxide is preferably 1-10 μm.

[0014] In an embodiment of the present invention, in step S1, after obtaining the dispersion liquid after the reaction, it is mixed with the carbon nanotube dispersion liquid, and ultrasonic stirring and vacuum filtration are performed to embed the formed particles into the interwoven network structure of the carbon nanotubes, and then freeze-dried to obtain a precursor freeze-dried powder.

[0015] In an embodiment of the present invention, in step S2, the carbonization heat treatment comprises: placing the precursor in a tube furnace, heating and keeping the temperature in an inert or nitrogen atmosphere, and then cooling to room temperature to obtain a silicon-carbon composite product; the inert atmosphere is preferably argon or helium;

[0016] The temperature of the heating and heat preservation is preferably 700-900°C.

[0017] In an embodiment of the present invention, in step S2, after obtaining the silicon-carbon composite product, a mixed acid consisting of concentrated sulfuric acid and concentrated nitric acid is added, the obtained acid mixture is ultrasonically treated at a constant temperature of 20-30°C, the reaction mixture is diluted with water, filtered, washed and dried to obtain a surface carboxylated silicon-carbon composite.

[0018] In an embodiment of the present invention, in step S3, the transition metal-carboxyl cluster is a carboxyl-containing Mn 12 Single molecule cluster crystal; the carboxyl-containing Mn 12 The single-molecule cluster crystals were obtained by the reaction of manganese acetate and potassium permanganate in an acetic acid aqueous solution.

[0019] In an embodiment of the present invention, in step S3, the carboxyl exchange reaction comprises: 12 The single-molecule cluster crystals were dissolved in acetonitrile solution to form Mn 12 An acetonitrile solution is prepared, and 0.1-0.5 g of the surface carboxylated silicon-carbon composite is added thereto, followed by ultrasonic reaction, and separation to obtain a modified silicon negative electrode material.

[0020] The present invention provides a lithium ion battery negative electrode, characterized in that the modified silicon negative electrode material described above or the modified silicon negative electrode material obtained by the preparation method described above is used as an active material.

[0021] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a separator therebetween, wherein the negative electrode is the lithium ion battery negative electrode described above.

[0022] In an embodiment of the present invention, the active material of the positive electrode is selected from at least one of lithium cobalt oxide, lithium nickel manganese oxide and nickel cobalt manganese ternary material;

[0023] The diaphragm is selected from at least one of a polyethylene diaphragm and a polypropylene diaphragm.

[0024] Compared with the prior art, the present invention provides a carboxylated carbon nanotube-coated SiO2 film anchored with a transition metal cluster containing rich carboxyl groups. x The present invention discloses a modified silicon negative electrode material, which is used as a modified silicon negative electrode material in a lithium ion battery, and also provides a method for preparing the modified silicon negative electrode material. In the present invention, a carboxyl exchange reaction can be used to anchor a carboxyl-rich transition metal monomolecular cluster on a carboxylated carbon nanotube and coat the carbon nanotube with a silicon oxide (SiO x ) surface, can make the lattice gap wider, reduce the impedance of lithium battery, improve ion conductivity and lithium ion diffusion rate, reduce polarization, thereby improving the cycle performance of the battery, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a SEM image of the carboxylated carbon nanotubes involved in the embodiment of the present invention;

[0026] Figure 2 is a SEM image of the modified carbon nanotube material involved in the embodiment of the present invention;

[0027] Figure 3 is an XRD diagram of the modified carbon nanotube material involved in the embodiment of the present invention;

[0028] Figure 4 2 is a SEM image of SiOx@PEI-PDA@CNT in some embodiments of the present invention. DETAILED DESCRIPTION

[0029] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the drawings and the like in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The invention provides a modified silicon negative electrode material, comprising: a silicon oxide substrate and modified carbon nanotubes coated on the surface of the silicon oxide substrate, wherein the modified carbon nanotubes are carboxylated carbon nanotubes anchored with transition metal-carboxyl clusters.

[0031] The modified silicon negative electrode material described in the embodiment of the present invention is silicon oxide (SiO x ) particles as the substrate, which is conducive to ensuring a high lithium storage capacity. In addition, the surface of the silicon oxide substrate is coated with modified carbon nanotubes, and the modified carbon nanotubes are carboxylated carbon nanotubes anchored with transition metal-carboxyl clusters, wherein the transition metal-carboxyl clusters are mainly carboxyl-containing Mn 12 Single-molecule clusters.

[0032] The modified silicon negative electrode material described in the embodiment of the present invention is a micro-nano material; the carbon nanotubes involved are mainly multi-walled carbon nanotubes (MWCNTs, referred to as CNTs, CNTs), and their typical tube diameter is 2-100nm. Carbon nanotubes have good electrical and mechanical properties. Carbon nanotubes will stretch slightly to control the volume expansion of silicon, and then return to their original shape, and can increase the conductivity of the material. The embodiment of the present invention includes carboxyl-functionalized carbon nanotubes, which can be referred to as carboxylated carbon nanotubes, which have stronger chemical reactivity.

[0033] In a preferred embodiment of the present invention, the modified carbon nanotubes are anchored with carboxyl-containing Mn 12 Single molecule cluster, the anchor can be a carboxyl-containing Mn 12 The monomolecular cluster is partially inserted into the carboxylated carbon nanotube, and some embodiments are characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD). Atomic cluster metal compounds are metal atom clusters that exist in an independent molecular state, and each metal atom cluster contains 3 or more metal atoms that are bonded to each other. The transition metal-carboxyl cluster is a transition metal monomolecular cluster containing a carboxyl group, which has a special structure and performance.

[0034] The modified silicon negative electrode material of the preferred embodiment of the present invention is anchored with Mn containing rich carboxyl groups. 12 Carboxylated carbon nanotubes coated with SiO x Anode materials, including carboxyl-rich Mn 12 The single-molecule clusters are anchored on carboxylated carbon nanotubes and coated on SiO x The surface of Mn 12 The single molecule cluster can widen the lattice gap, thereby reducing the impedance of the lithium battery, improving the ion conductivity and the lithium ion diffusion rate, reducing polarization, improving the cycle performance, etc. In addition, the modified silicon negative electrode material also contains a very small amount of nitrogen.

[0035] In addition, although some existing technologies can partially improve the conductivity by combining nano-silicon with carbon materials, the conductivity of silicon itself is poor, and it is easy to form isolated silicon particles after volume expansion, which reduces the overall conductivity. At the same time, the solid electrolyte interface (SEI) film on the silicon surface is unstable, and repeated formation and rupture consumes a large amount of lithium ions and electrolyte. When it is combined with positive electrode materials to form a full-electric battery (soft pack, square, cylindrical), the transition metal ions dissolved from the positive electrode will be deposited on the surface of the negative electrode material to cause side reactions, further destroying the SEI film and consuming active lithium, making the electrochemical reaction kinetics slow, affecting the coulomb efficiency and rate performance.

[0036] The modified silicon negative electrode material described in the embodiment of the present invention can reduce the stress of volume expansion of silicon material during the cycle, provide more variable space for material expansion, and prevent the particle rupture and material pulverization caused by volume expansion of silicon material and separation from the current collector during lithium ion insertion and extraction. 12 The single-molecule clusters are rich in carboxyl groups, which can complex the transition metal ions dissolved from the positive electrode material during the cycle, avoiding deposition on the negative electrode surface and inducing side reactions that further damage the SEI film, thicken the SEI, and ultimately cause rapid decay of the cycle capacity.

[0037] Furthermore, an embodiment of the present invention provides a method for preparing a modified silicon negative electrode material, comprising the following steps:

[0038] S1, mixing silicon oxide and a bonding polymer for reaction, and then embedding the formed particles into the interwoven network structure of carbon nanotubes to obtain a precursor;

[0039] S2, subjecting the precursor to carbonization heat treatment in an inert or nitrogen atmosphere, and then reacting with a mixed acid consisting of concentrated sulfuric acid and concentrated nitric acid to obtain a surface carboxylated silicon-carbon composite;

[0040] S3, forming a modified silicon negative electrode material by subjecting the surface carboxylated silicon-carbon composite to a carboxyl exchange reaction with a transition metal-carboxyl cluster.

[0041] The preferred embodiment of the present invention provides a method for anchoring Mn 12 Carboxylated carbon nanotubes coated with SiO x Preparation method of negative electrode material, the modified silicon negative electrode material is composed of Mn 12 The single-molecule cluster is anchored to the SiO-coated x The particles are composed of carboxylated CNTs, and the preparation method comprises the following steps:

[0042] Step 1: Preparation of SiOx@C@CNT: Add polyethyleneimine (PEI) solution to water (generally deionized water, the same below) to make the solution pH 8-9.5 in a weak alkaline state, and then add silicon oxide SiO x , continuous stirring to ensure the PEI and SiO x Then, dopamine hydrochloride (DA) is added to the mixed solution, preferably with ultrasonic stirring to ensure full polymerization of dopamine. x A cross-linked copolymer is generated on the particle surface (x in silicon oxide can be 1 and / or 2, which is well known to those skilled in the art and is not particularly limited). Finally, the particles are preferably centrifuged at 8000 rpm, the supernatant is discarded, and the particles are washed thoroughly with water, which is repeated 4 times to ensure that no cross-linked copolymer is formed on the SiO xThe polymerized substances on the particle surface were completely removed to obtain SiOx@PEI-PDA dispersion.

[0043] A certain amount of CNT dispersion is added to the dispersion after the above reaction, and the mixture is fully ultrasonicated and stirred. Then, the mixed dispersion is vacuum filtered to embed the SiOx@PEI-PDA particles into the interwoven network structure of the carbon nanotubes. The filter cake collected by filtration is preferably freeze-dried to obtain SiOx@PEI-PDA@CNT freeze-dried powder.

[0044] The precursor SiOx@PEI-PDA@CNT obtained in the above process is placed in a tubular furnace, and in an inert or nitrogen atmosphere, the temperature is increased to 700-900°C at a certain heating rate and then maintained at that temperature, and then the temperature is decreased to room temperature at a certain cooling rate, and finally a silicon-carbon composite product at the carbonization heat treatment temperature is obtained, which can be recorded as SiOx@C@CNT.

[0045] The obtained SiOx@C@CNT can be added to a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a ratio of 3:1, and then the SiOx@C@CNT / acid mixture is ultrasonically treated at a constant temperature of 20-30°C; the SiOx@C@CNT / acid mixture is diluted with water, filtered through a polycarbonate filter membrane, and washed with water three times to remove the strong acid remaining on the surface, and the filtered and washed solid is placed in a vacuum oven for drying, and the obtained carboxylated material is set aside.

[0046] Step 2: Mn 12 Preparation of single-molecule cluster crystals: Mn(CH3COO)2·4H2O is dissolved in 60% acetic acid solution (acetic acid solution is pure acetic acid added to distilled water to a concentration of 60% by mass); KMnO4 is preferably added to the mixed solution within 10 minutes, then stirred vigorously for 10 minutes, and after being placed in a cool place for 7 days, the reaction mixture is filtered, the crystals are retained and washed with acetone.

[0047] Step 3: Mn 12 Preparation of / SiOx@C@CNT: Take a certain mass of Mn 12 The single-molecule cluster crystals (black crystals) are added to the acetonitrile solution and stirred in a magnetic stirrer for 12 hours to fully dissolve. After stopping the stirring, the Mn 12 acetonitrile solution, and preferably add 0.1g-0.5g of SiOx@C@CNT prepared in step 1 to the acetonitrile solution, then ultrasonically react, and then stand for 24h. Finally, preferably centrifuge at 10000rpm, wash twice with acetonitrile solution, and then put into an oven for drying to obtain the target product Mn 12 / SiOx@C@CNT, which is a preferred modified silicon negative electrode material.

[0048] As a preferred method, the SiO2 with a particle size of 1-10 μm is used in the above step 1. x Materials: The molecular weight of polyethyleneimine can be between 300-600. SiO x The mass ratio of the material to dopamine hydrochloride is preferably 1:1, and ultrasonic stirring is performed for 24 hours. The solid content of the CNT dispersion can be 1-4%, and CNT accounts for 1% of SiO x 10%-50% of the material mass. As a preferred embodiment, in the above step 1, the inert atmosphere of the carbonization heat treatment is preferably argon or helium; the flow rate of the inert atmosphere or nitrogen atmosphere can be 100 sccm. As a preferred embodiment, in the above step 1, the heating rate is 5°C·min -1 , heat to 700-900℃ and keep for 2h, then press 5℃·min -1 The cooling rate dropped to room temperature.

[0049] As a preferred embodiment, in step 2, Mn is prepared 12 Single molecule cluster crystals, low cost.

[0050] As a preferred method, in step 3, Mn 12 Single molecule cluster crystal 1g; Mn 12 The amount of SiOx@C@CNT added to the acetonitrile solution is between 0.1g and 0.5g. As a preferred embodiment, in step 3, the dissolution and ultrasonic temperature involved is room temperature 20-30°C; the oven drying temperature can be 60-70°C.

[0051] In order to achieve the above-mentioned purpose of the invention, the present invention also provides a lithium-ion battery negative electrode, and a lithium-ion battery, wherein the lithium-ion battery comprises a positive electrode, a negative electrode, a separator therebetween, and an electrolyte, and the active material of the negative electrode is the modified silicon negative electrode material described above or the modified silicon negative electrode material obtained by the preparation method described above.

[0052] Preferably, the active material of the negative electrode is the above-mentioned Mn 12 / SiOx@C@CNT material, the negative electrode may also include a conductive agent SP, a binder carboxymethyl cellulose (CMC), styrene-butadiene latex (SBR), and polyacrylic acid (PAA). In the preferred negative electrode, active material: conductive agent SP: CMC: SBR: PAA = 95-96: 0.8-0.9: 0.7-0.9: 1-2: 1-2 (mass ratio).

[0053] In an embodiment of the present invention, the active material of the positive electrode is selected from at least one of lithium cobalt oxide (LCO), lithium nickel manganese oxide (LNMO) and nickel cobalt manganese ternary materials, for example, lithium cobalt oxide. In addition to the active material, the positive electrode also includes conventional conductive agents, binders, etc., conductive agents such as carbon nanotubes, binders such as polyvinylidene fluoride (PVDF). Preferably, in the positive electrode, the mass ratio of the positive electrode material LCO, the conductive agent SP CNTs, and the binder PVDF is 97-98:1-2:0.5-1:1.

[0054] In an embodiment of the present invention, the electrolyte is selected from a silicon negative electrode electrolyte containing a FEC additive. In a specific preferred electrolyte, the solute is lithium hexafluorophosphate (LiPF6), a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) is used as a solvent, and the volume ratio of the three can be 30:40:30, and the additives are fluoroethylene carbonate (FEC) and propane sultone (PS).

[0055] In an embodiment of the present invention, the diaphragm is selected from at least one of a polyethylene diaphragm and a polypropylene diaphragm. The diaphragm is preferably a polyethylene-coated alumina ceramic diaphragm with a thickness of 9 μm.

[0056] The preferred embodiment of the present invention prepares the lithium ion battery sample for the experiment, and the specific steps are as follows:

[0057] The positive electrode active material, conductive agent and binder are weighed and mixed according to a certain mass ratio. After mixing, an appropriate amount of N-methylpyrrolidone (NMP) is added to control the theoretical solid content to 50-60%. A vacuum defoamer is used to homogenize the positive electrode slurry, and the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 8-20 μm. After drying, rolling and cutting, a 50mm×70mm positive electrode sheet can be obtained.

[0058] The Mn prepared by the above method 12 / SiOx@C@CNT material is used as the active material of the negative electrode, the negative electrode active material, conductive agent, thickener, binder, etc. are mixed according to the mass ratio, water is added after the mixing is completed to control the theoretical solid content to 30-40%, and the negative electrode slurry is obtained by homogenization using a vacuum defoamer, and the negative electrode slurry is evenly coated on a copper foil with a thickness of 8-20μm, and after drying, rolling and cutting, a 52mm×72mm negative electrode sheet can be obtained. Preferably, the N / P ratio of the positive and negative electrodes is 1.1.

[0059] The polypropylene diaphragm or polyethylene diaphragm can be cut into a size of 55 mm×75 mm and vacuum-baked at 70°C for 48 hours to remove water.

[0060] A soft-pack laminated battery is made at an ambient dew point of ≤-45°C. The positive electrode, diaphragm, and negative electrode are stacked in order, with the positive and negative electrode tabs on the same side, so that the diaphragm is located between the positive and negative electrode sheets to play an isolating role, and a bare battery cell is obtained. The bare battery cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, and then injected with electrolyte after cooling to below 40°C. Among them, the electrolyte composition used is 1M LiPF6, the volume ratio of EC:DEC:EMC is 30:40:30, and the additives are 5% FEC and PS. Subsequently, packaging, high-temperature infiltration, formation, aging, secondary vacuum packaging, and capacity division are carried out to obtain an experimental battery.

[0061] Based on the modified silicon negative electrode material and the negative electrode thereof, the lithium-ion battery described in the embodiment of the present invention has good cycle performance, etc.

[0062] In order to better illustrate the present invention, the following examples are further illustrated. Unless otherwise specified, the various reagents and raw materials used in the present invention are commercially available products or products prepared by recognized methods, the molecular weight of polyethyleneimine is between 300-600, and the diaphragm is a polyethylene-coated alumina ceramic diaphragm with a thickness of 9 μm.

[0063] Example 1

[0064] Step 1: Preparation of SiOx@C@CNT: Add 0.02 g mL -1 5 mL of PEI solution was added to make the solution pH ≈ 9 in a weak alkaline state, and then 0.2 g of SiO x (particle size 1 ~ 10nm), continuous stirring to ensure that PEI and SiO x Then, 0.2 g of dopamine hydrochloride (DA) was added to the solution and ultrasonically stirred for 24 h to ensure full polymerization of dopamine. x Finally, the particles were centrifuged at 8000 rpm for 30 min, the supernatant was discarded, and the particles were washed thoroughly with deionized water. This process was repeated 4 times to ensure that no crosslinking occurred on the SiO x The polymerized substances on the surface of the particles were completely removed to obtain SiOx@PEI-PDA dispersion. 0.02 g of CNT dispersion was added to the dispersion, fully ultrasonicated and stirred, and then the dispersion was vacuum filtered to embed the SiOx@PEI-PDA particles into the interwoven network structure of carbon nanotubes. The filter cake collected by filtration was freeze-dried for 12 hours to obtain SiOx@PEI-PDA@CNT freeze-dried powder. The precursor SiOx@PEI-PDA@CNT obtained by the above process was placed in a tubular furnace and heated at 5 °C min in an inert atmosphere. -1 The temperature was raised to 700℃ at a rate of 200℃ and kept at this temperature for 2h, then heated at a rate of 5℃min-1 The cooling rate was reduced to room temperature, and the product at the heat treatment temperature was finally obtained, which was recorded as SiOx@C@CNT. The obtained SiOx@C@CNT was added to a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a ratio of 3:1, and then the SiOx@C@CNT / acid mixture was ultrasonically treated at a constant temperature of 25°C for 6 hours, and the SiOx@C@CNT / acid mixture was diluted with deionized water and filtered through a polycarbonate filter membrane, and washed with deionized water 3 times to wash away the strong acid remaining on the surface. The filtered and washed solid was placed in a vacuum oven for drying and set aside.

[0065] Step 2: Mn 12 Preparation of single-molecule cluster crystals: Mn(CH3COO)2·4H2O (10 g) was dissolved in 125 ml of 60% acetic acid solution. KMnO4 was added to the mixture within 10 minutes, and then stirred vigorously for 10 minutes. After being placed in a cool place for 7 days, the mixture was filtered to retain the crystals and washed with acetone.

[0066] Step 3: Mn 12 Preparation of / SiOx@C@CNT: Mn 12 Take 1g of black crystals and add them to 30ml of acetonitrile solution. Stir for 12h in a magnetic stirrer to fully dissolve them. After stopping stirring, filter with a 5μm filter head to obtain Mn 12 acetonitrile solution, and add 0.1g SiOx@C@CNT prepared in step 1 to the solution, then ultrasonically react for 1h, and then stand for 24h. Finally, centrifuge at 10000rpm, wash twice with acetonitrile solution and put into an oven for drying to obtain Mn 12 / SiOx@C@CNT-700 (corresponding to sintering temperature 700℃, and so on).

[0067] Prepare the experimental battery 1 sample, the specific steps are as follows:

[0068] The positive electrode material lithium cobalt oxide (LCO), the conductive agent carbon nanotube (CNT, NMP solution with a content of 5% by mass), and the binder polyvinylidene fluoride (PVDF, NMP solution with a content of 5% by mass) are weighed and mixed in a mass ratio of 98:0.8:1.2. After mixing, an appropriate amount of NMP is added to control the theoretical solid content to 55%. A vacuum defoamer is used to homogenize the positive electrode slurry, and the positive electrode slurry is evenly coated on a 9μm thick aluminum foil. After drying, rolling and cutting, a 50mm×70mm positive electrode sheet is obtained.

[0069] The negative electrode plate used in this embodiment 1 is made of Mn 12 / SiOx@C@CNT-700 material is used as the active material. The specific preparation is as follows: the active material, the conductive agent Super P, the thickener sodium carboxymethyl cellulose (CMC, the content is 1.5% by mass in deionized water solution), the binder styrene butadiene rubber (SBR, the content is 48% by mass in deionized water solution), polyacrylic acid (PAA, the content is 6% by mass in deionized water solution), and the single-walled carbon nanotube (CNT, the content is 0.4% by mass in deionized water solution) are mixed in a mass ratio of 95:0.9:1:1:2:0.1. After the mixing is completed, deionized water is added to control the theoretical solid content to 35%. The negative electrode slurry is obtained by homogenization using a vacuum defoamer, and the negative electrode slurry is evenly coated on a 9μm thick copper foil. After drying, rolling, and cutting, a 52mm×72mm negative electrode sheet is obtained. Among them, the N / P ratio of the positive and negative electrodes is 1.1.

[0070] The polyethylene diaphragm was cut into a size of 55 mm × 75 mm and vacuum-baked at 70°C for 48 h to remove water.

[0071] A soft-pack laminated battery is made at an ambient dew point of ≤-45°C. The positive electrode, diaphragm, and negative electrode are stacked in order, with the positive and negative electrode tabs on the same side, so that the diaphragm is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, and then injected with electrolyte after cooling to below 40°C. The electrolyte composition used is 1MLiPF6, the volume ratio of EC:DEC:EMC is 30:40:30, and the additives are 5% FEC and PS. Subsequently, packaging, high-temperature infiltration, formation, aging, secondary vacuum packaging, and capacity division are carried out to obtain the experimental battery 1.

[0072] Example 2

[0073] Step 1: Preparation of SiOx@C@CNT: Add 0.02 g mL -1 5 mL of PEI solution was added to make the solution pH ≈ 9 in a weak alkaline state, and then 0.2 g of SiO x , keep stirring to ensure that PEI and SiO x Then, 0.2 g of dopamine hydrochloride was added to the solution and ultrasonically stirred for 24 h to ensure full polymerization of dopamine. x Finally, the particles were centrifuged at 8000 rpm for 30 min, the supernatant was discarded, and the particles were washed thoroughly with deionized water. This process was repeated 4 times to ensure that no crosslinking occurred on the SiO xThe polymerized substances on the surface of the particles were completely removed to obtain SiOx@PEI-PDA dispersion. 0.04 g of CNT dispersion was added to the dispersion, fully ultrasonicated and stirred, and then the dispersion was vacuum filtered to embed the SiOx@PEI-PDA particles into the interwoven network structure of carbon nanotubes. The filter cake collected by filtration was freeze-dried for 12 hours to obtain SiOx@PEI-PDA@CNT freeze-dried powder. The precursor SiOx@PEI-PDA@CNT obtained by the above process was placed in a tubular furnace and heated at 5 °C min in an inert atmosphere. -1 The temperature was raised to 900℃ at a rate of 2h and then heated at 5℃min -1 The cooling rate was reduced to room temperature, and the product at the heat treatment temperature was finally obtained, which was recorded as SiOx@C@CNT. The obtained SiOx@C@CNT was added to a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a ratio of 3:1, and then the SiOx@C@CNT / acid mixture was ultrasonically treated at a constant temperature of 25°C for 6 hours, and the SiOx@C@CNT / acid mixture was diluted with deionized water and filtered through a polycarbonate filter membrane, and washed with deionized water 3 times to wash away the strong acid remaining on the surface. The filtered and washed solid was placed in a vacuum oven for drying and set aside.

[0074] Step 2: Mn 12 Preparation of single-molecule cluster crystals: Mn(CH3COO)2·4H2O (10 g) was dissolved in 125 ml of 60% acetic acid solution. KMnO4 was added to the mixture within 10 minutes, and then stirred vigorously for 10 minutes. After being placed in a cool place for 7 days, the mixture was filtered, the crystals were retained, and washed with acetone.

[0075] Step 3: Mn 12 Preparation of / SiOx@C@CNT: Mn 12 Take 1g of the black crystals and add them to 30ml of acetonitrile solution. Stir for 12h in a magnetic stirrer to fully dissolve them. After stopping stirring, filter with a 5μm filter head to obtain Mn 12 acetonitrile solution, and add 0.1g SiOx@C@CNT prepared in step 1 to the solution, then ultrasonically react for 1h, and then stand for 24h. Finally, centrifuge at 10000rpm, wash twice with acetonitrile solution and put into an oven for drying to obtain Mn 12 / SiOx@C@CNT-900.

[0076] Experimental battery 2 was prepared according to the method of Example 1, except that the negative electrode active material was Mn prepared in Example 2. 12 / SiOx@C@CNT-900.

[0077] Example 3

[0078] Step 1: Preparation of SiOx@C@CNT: Add 0.02 g mL -1 5 mL of PEI solution was added to make the solution pH ≈ 9 in a weak alkaline state, and then 0.2 g of SiO x , keep stirring to ensure that PEI and SiO x Then, 0.2 g of dopamine hydrochloride was added to the solution and ultrasonically stirred for 24 h to ensure full polymerization of dopamine. x Finally, the particles were centrifuged at 8000 rpm for 30 min, the supernatant was discarded, and the particles were washed thoroughly with deionized water. This process was repeated 4 times to ensure that no crosslinking occurred on the SiO x The polymerized substances on the surface of the particles were completely removed to obtain SiOx@PEI-PDA dispersion. 0.1 g of CNT dispersion was added to the dispersion, fully ultrasonicated and stirred, and then the dispersion was vacuum filtered to embed the SiOx@PEI-PDA particles into the interwoven network structure of carbon nanotubes. The filter cake collected by filtration was freeze-dried for 12 hours to obtain SiOx@PEI-PDA@CNT freeze-dried powder. The precursor SiOx@PEI-PDA@CNT obtained by the above process was placed in a tubular furnace and heated at 5 °C min in an inert atmosphere. -1 The temperature was raised to 900℃ at a rate of 2h and then heated at 5℃min -1 The cooling rate was reduced to room temperature, and the product at the heat treatment temperature was finally obtained, which was recorded as SiOx@C@CNT. The obtained SiOx@C@CNT was added to a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a ratio of 3:1, and then the SiOx@C@CNT / acid mixture was ultrasonically treated at a constant temperature of 25°C for 6 hours, and the SiOx@C@CNT / acid mixture was diluted with deionized water and filtered through a polycarbonate filter membrane, and washed with deionized water 3 times to wash away the strong acid remaining on the surface. The filtered and washed solid was placed in a vacuum oven for drying and set aside.

[0079] Step 2: Mn 12 Preparation of single-molecule cluster crystals: Mn(CH3COO)2·4H2O (10 g) was dissolved in 125 ml of 60% acetic acid solution. KMnO4 was added to the mixture within 10 minutes, and then stirred vigorously for 10 minutes. After being placed in a cool place for 7 days, the mixture was filtered, and the crystals were retained and washed with acetone.

[0080] Step 3: Mn 12 Preparation of / SiOx@C@CNT: Mn 12 Take 1g of the black crystals and add them to 30ml of acetonitrile solution. Stir for 12h in a magnetic stirrer to fully dissolve them. After stopping stirring, filter with a 5μm filter head to obtain Mn 12acetonitrile solution, and add 0.5g of SiOx@C@CNT prepared in step 1 to the solution, then ultrasonically react for 1h, and then stand for 24h. Finally, centrifuge at 10000rpm, wash twice with acetonitrile solution, and put into an oven for drying to obtain Mn 12 / SiOx@C@CNT-0.5.

[0081] Experimental battery 3 was prepared according to the method of Example 1, except that the negative electrode active material was Mn prepared in Example 3. 12 / SiOx@C@CNT-0.5.

[0082] Example 4

[0083] First, prepare Mn 12 Crystal (same as step 2 of Example 1), obtain Mn 12 1 g of black crystals was added to 30 ml of acetonitrile solution and stirred in a magnetic stirrer for 12 h to fully dissolve. After stopping stirring, the mixture was filtered using a 5 μm filter head to obtain Mn 12 acetonitrile solution, and add 0.1g of carboxylated carbon nanotubes to the solution and then ultrasonically react for 1h, and then stand for 24h. Finally, centrifuge and wash twice with acetonitrile solution, and then put it in an oven for drying to obtain the target product Mn 12 / C-CNTs.

[0084] Experimental battery 4 was prepared according to the method of Example 1, except that the negative electrode active material was Mn prepared in Example 4. 12 / C-CNTs. To explore the 12 The microstructure of the / C-CNTs sample was tested by SEM. Figure 1 , 2 The prepared product was analyzed by XRD. Figure 3 shown.

[0085] Comparative Example 1

[0086] Using untreated SiO xAs active materials, it was mixed with conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC, 1.5% by mass in deionized water solution), binder styrene butadiene rubber (SBR, 48% by mass in deionized water solution), polyacrylic acid (PAA, 6% by mass in deionized water solution), and single-walled carbon nanotubes (CNT, 0.4% by mass in deionized water solution) in a mass ratio of 95:0.9:1:1:2:0.1. After mixing, deionized water was added to control the theoretical solid content to 35%. A vacuum defoamer was used to homogenize the negative electrode slurry, and the negative electrode slurry was evenly coated on a copper foil with a thickness of 9 μm. After drying, rolling, and cutting, a 52 mm × 72 mm negative electrode sheet was obtained. The N / P ratio of the positive and negative electrodes is 1.1.

[0087] The polyethylene diaphragm was cut into a size of 55 mm × 75 mm and vacuum-baked at 70°C for 48 h to remove water.

[0088] A soft-pack laminated battery is made at an ambient dew point of ≤-45°C. The positive electrode, diaphragm, and negative electrode are stacked in order, with the positive and negative electrode tabs on the same side, so that the diaphragm is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, and then injected with electrolyte after cooling to below 40°C. The electrolyte composition used is 1MLiPF6, the volume ratio of EC:DEC:EMC is 30:40:30, and the additives are 5% FEC and PS. Subsequently, packaging, high-temperature infiltration, formation, aging, secondary vacuum packaging, and capacity division are carried out to obtain the experimental battery 5.

[0089] Comparative Example 2

[0090] Preparation process: Add 0.02 g mL into 30 mL of deionized water -1 5 mL of PEI solution was added to make the solution pH ≈ 9 in a weak alkaline state, and then 0.2 g of SiO x , keep stirring to ensure that PEI and SiO x Then, 0.2 g of dopamine hydrochloride was added to the solution and ultrasonically stirred for 24 h to ensure full polymerization of dopamine. x Finally, the particles were centrifuged at 8000 rpm for 30 min, the supernatant was discarded, and the particles were washed thoroughly with deionized water. This process was repeated 4 times to ensure that no crosslinking occurred on the SiO xThe polymerized substances on the surface of the particles were completely removed to obtain SiOx@PEI-PDA dispersion. 0.04 g of CNT dispersion was added to the dispersion, fully ultrasonicated and stirred, and then the dispersion was vacuum filtered to embed the SiOx@PEI-PDA particles into the interwoven network structure of carbon nanotubes. The filter cake collected by filtration was freeze-dried for 12 hours to obtain SiOx@PEI-PDA@CNT freeze-dried powder. The precursor Si@PEI-PDA@CNT obtained by the above process was placed in a tubular furnace and heated at 5 °C min in an inert atmosphere. -1 The heating rate was raised to 800℃ and kept for 2h, then the temperature was increased at 5℃min -1 The cooling rate was reduced to room temperature, and the product at the heat treatment temperature was finally obtained, which was recorded as SiOx@C@CNT. The obtained SiOx@C@CNT was added to a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a ratio of 3:1, and then the SiOx@C@CNT / acid mixture was ultrasonically treated at a constant temperature of 25°C for 6 hours, and the SiOx@C@CNT / acid mixture was diluted with deionized water and filtered through a polycarbonate filter membrane, and washed with deionized water 3 times to wash away the strong acid remaining on the surface. The filtered and washed solid was placed in a vacuum oven for drying and set aside.

[0091] Experimental battery 6 was prepared according to the method of Example 1, except that SiOx@C@CNT prepared in Comparative Example 1 was used as the active material.

[0092] Comparative Example 3

[0093] Carboxylated carbon nanotubes purchased on the market were used as active materials, and were mixed with conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC, 1.5% by mass in deionized water solution), binder styrene butadiene rubber (SBR, 48% by mass in deionized water solution), polyacrylic acid (PAA, 6% by mass in deionized water solution), and single-walled carbon nanotubes (CNT, 0.4% by mass in deionized water solution) in a mass ratio of 95:0.9:1:1:2:0.1. After mixing, deionized water was added to control the theoretical solid content to 35%. A vacuum defoamer was used to homogenize the negative electrode slurry, and the negative electrode slurry was evenly coated on a copper foil with a thickness of 9 μm. After drying, rolling, and cutting, a 52 mm × 72 mm negative electrode sheet was obtained. The N / P ratio of the positive and negative electrodes was 1.1.

[0094] The polyethylene diaphragm was cut into a size of 55 mm × 75 mm and vacuum-baked at 70°C for 48 h to remove water.

[0095] A soft-pack laminated battery was made at an ambient dew point of ≤-45°C. The positive electrode sheet, diaphragm, and negative electrode sheet were stacked in order, with the positive and negative electrode tabs on the same side, so that the diaphragm was in the middle of the positive and negative electrode sheets to play an isolating role, and a bare cell was obtained. The bare cell was placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, and then injected with electrolyte after cooling to below 40°C. The electrolyte composition used was 1MLiPF6, the volume ratio of EC:DEC:EMC was 30:40:30, and the additives were 5% FEC and PS. Subsequently, packaging, high-temperature infiltration, formation, aging, secondary vacuum packaging, and capacity division were carried out to obtain the experimental battery 7.

[0096] Battery Test

[0097] 1. Normal temperature cycle test

[0098] Xinwei test program settings: charge at a constant current and constant voltage of 1C in a constant temperature room at 25℃, with a cut-off voltage of 4.48V and a cut-off current of 0.05C, and then discharge at a constant current of 1C to 3.0V, with 800 cycles, to obtain the capacity retention rate of different formulations at 25℃.

[0099] 2. High temperature cycle test

[0100] The Xinwei test program setting is: charging at a constant current and constant voltage of 1C in a constant temperature box at 45℃, with a cut-off voltage of 4.48V and a cut-off current of 0.05C, and then discharging at a constant current of 1C to 3.0V, with 600 cycles, to obtain the capacity retention rate of different formulations at 45℃.

[0101] Capacity retention rate = 400th cycle discharge capacity / initial discharge capacity*100%.

[0102] 3. High temperature storage performance test

[0103] The battery was charged and discharged at 1C rate for one cycle at 25℃, and the discharge capacity was recorded. Then the battery was charged at 1C constant current until it was charged to 50% SOC. The battery DCIR was tested at 50% SOC. Then the battery was charged at 1C constant current and constant voltage, with a voltage of 4.48V and a cut-off current of 0.05C. The battery was stored in a high-temperature explosion-proof box at 60℃ for one week, and then discharged at 1C to 3V at 25℃. Then the battery was charged and discharged at 1C for one cycle, and the DCIR was tested at 50% full charge. The capacity retention rate, capacity recovery rate and internal resistance growth rate were calculated.

[0104] Capacity recovery rate = discharge capacity in the second cycle after high-temperature storage / discharge capacity in the last week before high-temperature storage * 100%;

[0105] DCIR test method: At 50% SOC, the battery is discharged at 0.1C for 10s and 1C for 1s; DCIR = voltage difference / current difference. The test results are as follows:

[0106] Table 1 Comparison of experimental battery performance of embodiments of the present invention

[0107]

[0108] From the above test results, it can be seen that Example 1 exhibits the best performance. By comparing Example 1 with Comparative Examples 1 and 2, it can be shown that the carboxyl exchange reaction can be used to make the carboxyl-rich Mn 12 The single molecule cluster is anchored on the carbon negative electrode material, Mn 12 The single-molecule cluster can widen the lattice gap, reduce the impedance of lithium batteries, improve ion conductivity and lithium ion diffusion rate, reduce polarization, and improve cycle performance. At the same time, it can reduce the stress of volume expansion of silicon negative electrode materials during the cycle, and prevent the abnormal expansion of the battery cell caused by particle rupture, material pulverization and separation from the current collector due to volume expansion of silicon materials during lithium ion deintercalation. Anchored Mn 12 The monomolecular clusters are rich in carboxyl groups, which can complex the transition metal ions dissolved from the positive electrode materials during the cycle, avoiding deposition on the negative electrode surface to cause damage to the SEI film, making the SEI thicker and eventually causing capacity decay. 12 The best effect is achieved when the addition amount is 0.1g.

[0109] The comparison between Example 4 and Comparative Example 3 can better illustrate that Mn 12 Advantages: Figure 1 These are carboxylated carbon nanotubes. From the picture, we can see that the nanotubes are relatively thin and curved, and appear to be in the shape of a hair ball. Figure 2 is Mn at different magnifications 12 / C-CNTs SEM image shows that the nanotubes are uniform in thickness and thicken at the head of the tube. It is inferred that the carboxyl content of this part is the highest. The position of Mn at the head of the nanotube is 12 The area where the Figure 3 As shown, the target sample Mn 12 The XRD diffraction pattern of / C-CNTs was compared with the standard card of carbon nanotubes PDF#41-1487, and it was found that the peak positions were consistent. The main diffraction peak at 26.2° obviously shifted to a smaller angle, indicating that after anchoring Mn 12 Later, the lattice gap becomes larger, which is caused by the small molecular size of Mn 12 The molecular clusters are partially inserted into the carboxylated carbon nanotubes. Figure 4 This is the SEM image of SiOx@PEI-PDA@CNT in Example 1, showing the composite morphology of the material.

[0110] In summary, according to the comparative examples and the data results of the examples, it can be seen that the Mn containing rich carboxyl groups proposed in the present invention12 Single-molecule cluster anchoring of silicon-carbon negative electrode materials can further improve the high-temperature cycling and high-temperature storage performance of the battery.

[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A modified silicon negative electrode material, characterized in that: include: A silicon oxide substrate and a modified carbon nanotube coated on the surface of the silicon oxide substrate, wherein the modified carbon nanotube is a carboxylated carbon nanotube anchored with a transition metal-carboxyl cluster.

2. A method for preparing a modified silicon negative electrode material, characterized in that: The following steps are involved: S1, mixing silicon oxide and a bonding polymer for reaction, and then embedding the formed particles into the interwoven network structure of carbon nanotubes to obtain a precursor; S2, subjecting the precursor to carbonization heat treatment in an inert or nitrogen atmosphere, and then reacting with a mixed acid consisting of concentrated sulfuric acid and concentrated nitric acid to obtain a surface carboxylated silicon-carbon composite; S3, forming a modified silicon negative electrode material by subjecting the surface carboxylated silicon-carbon composite to a carboxyl exchange reaction with a transition metal-carboxyl cluster.

3. The preparation method according to claim 2, characterized in that: In step S1, the adhesive polymer is polyethyleneimine and polydopamine; the mixing reaction of the silicon oxide and the adhesive polymer comprises: mixing the silicon oxide, polyethyleneimine and dopamine hydrochloride in water, reacting by ultrasonic stirring, and separating and washing to obtain the dispersion after the reaction; The particle size of the silicon oxide is preferably 1-10 μm.

4. The preparation method according to claim 3, characterized in that: In step S1, after the dispersion liquid after the reaction is obtained, it is mixed with the carbon nanotube dispersion liquid, ultrasonically stirred and vacuum filtered to embed the formed particles into the interwoven network structure of the carbon nanotubes, and then freeze-dried to obtain a precursor freeze-dried powder.

5. The preparation method according to claim 1, characterized in that: In step S2, the carbonization heat treatment comprises: placing the precursor in a tube furnace, heating and keeping the temperature in an inert or nitrogen atmosphere, and then cooling to room temperature to obtain a silicon-carbon composite product; the inert atmosphere is preferably argon or helium; The temperature of the heating and heat preservation is preferably 700-900°C.

6. The preparation method according to claim 5, characterized in that: In step S2, after obtaining the silicon-carbon composite product, a mixed acid consisting of concentrated sulfuric acid and concentrated nitric acid is added, and the obtained acid mixture is ultrasonically treated at a constant temperature of 20-30° C., the reaction mixture is diluted with water, filtered, washed, and dried to obtain a surface carboxylated silicon-carbon composite.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In step S3, the transition metal-carboxyl cluster is a carboxyl-containing Mn 12 Single molecule cluster crystal; the carboxyl-containing Mn 12 The single-molecule cluster crystals were obtained by the reaction of manganese acetate and potassium permanganate in an acetic acid aqueous solution.

8. The preparation method according to claim 7, characterized in that: In step S3, the carboxyl exchange reaction comprises: 12 The single-molecule cluster crystals were dissolved in acetonitrile solution to form Mn 12 An acetonitrile solution is prepared, and 0.1-0.5 g of the surface carboxylated silicon-carbon composite is added thereto, followed by ultrasonic reaction, and separation to obtain a modified silicon negative electrode material.

9. A negative electrode for a lithium ion battery, characterized in that: The modified silicon negative electrode material according to claim 1 or the modified silicon negative electrode material obtained by the preparation method according to any one of claims 2 to 8 is used as the active material.

10. A lithium ion battery comprising a positive electrode, a negative electrode and a separator therebetween, characterized in that: The negative electrode is the negative electrode of the lithium ion battery according to claim 9; The active material of the positive electrode is preferably at least one of lithium cobalt oxide, lithium nickel manganese oxide and nickel cobalt manganese ternary material; The diaphragm is preferably one of a polyethylene diaphragm and a polypropylene diaphragm.